2024
DOI: 10.5194/egusphere-2023-2981
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reviews and syntheses: Review of proxies for low-oxygen paleoceanographic reconstructions 

Babette Hoogakker,
Catherine Davis,
Yi Wang
et al.

Abstract: Abstract. A growing body of observations reveals rapid changes in both the total inventory and distribution of marine oxygen over the later half of the 21st century, leading to increased interest in extending oxygenation records into the past. Use of paleo-oxygen proxies have the potential to extend the spatial and temporal range of current records, bound pre-anthropogenic baselines, provide datasets necessary to test climate models under different boundary conditions, and ultimately understand how ocean oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 613 publications
0
2
0
Order By: Relevance
“…Specifically, the archives studied were planktic foraminifera (Winkelbauer et al, 2023), deep-sea bamboo and scleractinian corals (Sun et al, 2023), and ancient bulk carbonate rocks (He et al, 2022). An important finding is that, while benthic and planktic foraminifera from core-tops are known to record iodate variations of the overlying water column (reviewed in Hoogakker et al, 2024), foraminifera from plankton tows demonstrated littleto-no iodine incorporation regardless of local iodate abundance (Winkelbauer et al, 2023). This finding highlights the need for future work to address at what stagebetween living, postmortem, and diagenesisiodate is incorporated into foraminiferal tests.…”
mentioning
confidence: 99%
“…Specifically, the archives studied were planktic foraminifera (Winkelbauer et al, 2023), deep-sea bamboo and scleractinian corals (Sun et al, 2023), and ancient bulk carbonate rocks (He et al, 2022). An important finding is that, while benthic and planktic foraminifera from core-tops are known to record iodate variations of the overlying water column (reviewed in Hoogakker et al, 2024), foraminifera from plankton tows demonstrated littleto-no iodine incorporation regardless of local iodate abundance (Winkelbauer et al, 2023). This finding highlights the need for future work to address at what stagebetween living, postmortem, and diagenesisiodate is incorporated into foraminiferal tests.…”
mentioning
confidence: 99%
“…Specifically, the archives studied were planktic foraminifera (Winkelbauer et al, 2023), deep-sea bamboo and scleractinian corals (Sun et al, 2023), and ancient bulk carbonate rocks (He et al, 2022). An important finding is that, while benthic and planktic foraminifera from core-tops are known to record iodate variations of the overlying water column (reviewed in Hoogakker et al, 2024), foraminifera from plankton tows demonstrated littleto-no iodine incorporation regardless of local iodate abundance (Winkelbauer et al, 2023). This finding highlights the need for future work to address at what stagebetween living, postmortem, and diagenesisiodate is incorporated into foraminiferal tests.…”
mentioning
confidence: 99%